Aktiviti Fizikal Untuk Warga Emas (English version) - Makhtar, Aniawanis; Syed Elias, Sharifah Munirah (2021)
KTP is a knowledge transfer programme by the academician IIUM to volunteers of the Department of Social Welfare. The video of physical activity for older people is a part of intellectual property (IP) required to be produced under the allocation of the KTP- RIGS (KTP-RIGS 18-011-0011) grant. The video is prepared based on the need of older people in terms of the benefits of physical activity. The program of 'Program Kesihatan Fizikal dan Mental Sepanjang Hayat 2020' has been conducted into 2 phases. First phases on 21 August 2019 at Pusat Aktiviti Warga Emas, Kompleks Penyayang Kuantan Pahang and second phases through online platform (Facebook and YouTube live) on 4th February 2021.